Pop-up library - Husin, Norfatahiah; Mohd Shafie, Muhammad Shafiq Farhan; Mohd Roshidi, Muhammad Danish Aiman; Mohd Shafie, Muhammad Shafiq Fahmi (Universiti Teknologi MARA, Kedah, 2017)
Mobile library has been a common service by public libraries all over the world in the form of bus and van. The purpose is to disseminate information packages to users distance from the library. However the pop-up library is an innovative effort to distribute library materials in school library where a mobile compact box could be transformed into multi-function small mobile library. The box in its mobile format is movable and could be located and re-located in different places within the school compound. The compact box could be opened from various sides of the box where each side will have its own compartments containing different kind of library information package and library facilities. For instance the left side contain compartments with library reading materials such as books and magazines. The right hand side of the box contains compartments with educational games. The middle part of the box contains display monitor to view visual collections and slide show. The library in box format is movable and could be transformed from a box into multiple form of library facilities containing library materials and library facilities. It can goes to various locations within the school.